Arsenic treatment and power generation with a dual-chambered fuel cell with anionic and cationic membranes using NaHCO3 anolyte and HCl or NaCl catholyte. (April 2017) - Maitlo, Hubdar Ali; Kim, Jung Hwan; Park, Joo Yang
Abstract: Dual-chambered fuel cells with an iron anode and an air-carbon cathode separated by an ion exchange membranes have been used to treat arsenate during power production. To select an effective catholyte, the dual-chambered fuel cell consisted 90 mL of 0.1 M HCl or 0.5 M NaCl as the catholyte and 1 L of 0.1 M NaHCO3 as the anolyte at an initial pH 5. The 0.1 M HCl was an effective catholyte, with which 1 ppm arsenate in 1 L of anolyte was reduced to 5 ppb in 1 h, and the maximum power density was about 6.3 w/m 2 with an anion exchange membrane fuel cell (AEM_FC) and 4.4 w/m 2 with a cation exchange membrane fuel cell (CEM_FC). Therefore, 90 mL of 0.1 M HCl was used as a catholyte to treat 20 L of 0.1 M NaHCO3 anolyte containing 1 ppm arsenate at an initial pH of 5 or 7. The arsenate level at pH 5 decreased to less than 5 ppb in 4 h, and the maximum power density was 5.9 W/m 2 and 4.7 W/m 2 with AEM_FC and CEM_FC, respectively. When using 0.01 M NaHCO3 as the anolyte at pH 5, arsenate was reduced to less than 5 ppb in 8 and 24 h for AEC_FC and CEM_FC, respectively. However, when using an anolyte at pH 7, arsenate could not be effectively removed in 24 h. Therefore, when using carbonate as an anolyte, the solution should be adjusted to a weakly acidic pH in order to remove arsenate. Highlights: The iron-air dual-chambered fuel cell with AEM and CEM was used to treat arsenate. The 0.1 M HCl was an effective cathode electrolyte. The 1 ppm arsenate form 20 L of wastewater was reduced to less than 5 ppb in 4 h. The maximum power density was 5.9 W/m 2 and 4.7 W/m 2 with AEC_FC and CEM_FC. The iron-air dual-chambered fuel cell has possibility of real-world applications.